LEARNING INNOVATION THROUGH YOU-TUBE VLOG IN ERA 4.0 - Arsal , Thriwaty; Sunarjan, YYFR.; Karamina, Sharfina (International Journal of Psychosocial Rehabilitation, 2020)
Learning innovations need to be done by teachers in accordance with the development of science and technology so that teachers do not experience a shift in role. The purpose of this research is to analyze the learning innovation through You-Tube Vlog. Innovative learning models have several criteria that must be taken into consideration, among others; teacher can understand and achieve the learning objectives in each learning process, students’ pro-active involvement in the learning process at school, teacher helps students to be capable to make positive behavioral changes in various aspects of life. There are several You-Tube Vlog criteria which can be used as learning media by teachers, namely: You-Tube vlogs that are played in learning in class are adjusted to the material that is ongoing in the class’ learning process. The You-Tube Vlogs that are played in the classroom are not limited to learning videos but also include those of motivational video for students. You-Tube Vlogs can be employed to provide illustrations of learning material. However, teacher must also consider the duration of the You-Tube Vlog. The employment of You-Tube Vlog-based learning media used by teachers also changes the existing learning methods from those that are previously used through Problem- Based Learning (PBL) method or other methods in accordance with the learning material by giving lectures into audio-visual media learning method in the form of You-Tube Vlogs. The conclusion of this research is that learning innovation can be conducted by teachers by utilizing the development of science and technology, such as with the help of You-Tube Vlog learning media. You-Tube vlogs help teachers become more innovative and can create a pleasant learning atmosphere in the classroom, also capable to shape positive behavior changes in students.